Radiation induced valvular disease: the internist's prospective. Issue 1 (22nd January 2019) - Kumar, Sundeep; Patel, Hiren; Paulson, Joyce; Gros, Bernard
Abstract : Radiation-induced cardiac injury entails a wide spectrum of cardiovascular complications such as cardiomyopathy and valvular diseases among others. We present the internist's perspective and the challenges faced in managing these patients. There are guidelines addressing radiation-induced valvular disease (RIVD) including screening and treatment, but are often unrecognised by most internist's practice. A thorough cardiovascular examination and screening echocardiography may detect RIVD at an earlier stage. Early screening with transthoracic echocardiogram should be considered in asymptomatic or low-risk patients and more frequently in symptomatic and high-risk patients. The internists should educate their patients with prior chest irradiation, regarding the possible radiation related adverse cardiovascular effects and recommended screening. Lifestyle changes and aggressive cardiovascular risk modification should be emphasised, as concomitant hypertension, coronary artery disease and cardiomyopathy can have unfavourable effects in these patients.